Mathematical Literacy Skills of Fifth Grade Elementary School Students: A Case Study in Pekanbaru - Muhammad Jaya Adi Putra; Tri Agmadya; Syahrilfuddin Syahrilfuddin (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2021)
This study aims to identify and describe the mathematical literacy skills of fifth grade elementary school students. This study was conducted in one of the primary school in Pekanbaru from January to March 2020. The type of research used was a case study. The subject of this research was 37 fifth grade elementary school students. The instrument was arranged referring to the questions issued by PISA. After the instrument were validated by two experts and tested on students, the next step was used to retrieve data. The data collected is then grouped and categorized according to the device that has been created. The results of the data processing showed that most of the subjects had not been able to answer the questions at level 4 or above, while for the answered level it was broken down as follows; the mathematical literacy achievement of fifth grade elementary school students that reached level 1 were 38%, in level 2 there were 54%, and in level 3 there were 8%. From these data results, it appears that in general the fifth-grade elementary school students have a very low level in mathematical literacy skills, meaning that the learning technique they have gained so far has not been able to build mathematical literacy skills.